Pengaruh Pengetahuan, Kepercayaan dan Lokasi Terhadap Minat Membayar Zakat Melalui Badan Amil Zakat Nasional (BAZNAS) Kabupaten Tebo: Studi pada Masyarakat Kecamatan Tebo Tengah - Fery Adriansyah,; Ridhwan,; Aditya Pratama, (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Muslims are required to pay zakat for those who have property that meets the provisions of Islamic law. The main function of zakat is as an instrument in encouraging the economy of the less fortunate community. One of the institutions that manages zakat, infaq and alms on a large scale is the national zakat agency BAZNAS. However, currently the community in Tebo Tengah District does not fully participate in paying zakat through the Tebo Regency National Zakat Agency, it is suspected that knowledge, belief and location are factors that influence the interest of the community in paying their zakat. Thus, it has an impact on the level of fundraising at BAZNAS Tebo Regency. The purpose of this study was to determine the effect of the relationship between the variables of knowledge, belief and location on the interest of the Tebo Tengah District community in paying their zakat at BAZNAS Tebo Regency, with a sample size of 100 respondents. This study uses quantitative methods and data analysis techniques using SPSS 25. The results of this study indicate that the partial test (t) shows that the knowledge variable has no effect on the interest variable, while the belief variable and location variable have a significant effect on the interest variable. The simultaneous test (f) shows that the variables of knowledge, trust and location together have a significant influence on the variable of people's interest in paying zakat to the national zakat collection agency in Tebo Regency.